In silico Derivation of HLA-Specific Alloreactivity Potential from Whole Exome Sequencing of Stem-Cell Transplant Donors and Recipients: Understanding the Quantitative Immunobiology of Allogeneic Transplantation - Jameson-Lee, Max; Koparde, Vishal; Griffith, Phil; Scalora, Allison F.; Sampson, Juliana K.; Khalid, Haniya; Sheth, Nihar U.; Batalo, Michael; Serrano, Myrna G.; Roberts, Catherine H.; Hess, Michael L.; Buck, Gregory A.; et al. (Frontiers in Immunology, 2014)
Donor T cell mediated graft versus host effects (GVH) may result from the aggregate alloreactivity to minor histocompatibility antigens (mHA) presented by the HLA molecules in each donor-recipient pair undergoing stem cell transplantation (SCT). Whole exome sequencing has previously demonstrated a large number of nonsynonymous single nucleotide polymorphisms (SNP) present in HLA-matched recipients of SCT donors (GVH direction). The nucleotide sequence flanking each of these SNPs was obtained and the amino acid sequence determined. All the possible nonameric-peptides incorporating the variant amino acid resulting from these SNPs were interrogated in-silico for their likelihood to be presented by the HLA class I molecules using the Immune Epitope Database stabilized matrix method (SMM) and NetMHCpan algorithms. The SMM algorithm predicted that a median of 18,396 peptides weakly bound HLA class I molecules in individual SCT recipients, and 2,254 peptides displayed strong binding. A similar library of presented peptides was identified when the data was interrogated using the NetMHCpan algorithm. The bioinformatic algorithm presented here demonstrates that there may be a high level of mHA variation in HLA-matched individuals, constituting an HLA-specific alloreactivity potential.